Re-layout of Temporary Storage Area for Toxic and Hazardous Waste using 5S (Seiri, Seiton, Seiso, Seiketsu, Sitsuke) - Muhammad Ilham Adelino; Meldia Fitri; Ayu Sundari (Universitas Diponegoro, 2021)
One of the industries that produces toxic and hazardous waste is rubber industry. This study was conducted in PT. Famili Raya. The problem was toxic and hazardous waste placed in an irregular placement and no follow the government regulations for storing and managing. This aims of this study were to redesign temporary storage area for hazardous waste based on 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) and the regulation, Minister of Environment and Forestry No. 12/2020. The object of this study was temporary storage area for toxic and hazardous waste in PT. Famili Raya. The data used were current condition, actual dimensions of temporary storage area, dimensions of waste, input and output data, and dimensions of a forklift. The results obtained were the proposed layout using the 5S approach could be used to redesign the storage layout in the temporary storage area. Space utility could be reduced by 32,67%. The decrease in space utility did not reduce the maximum storage capacity for used batteries, used tubular lamp, used oil waste, and turpentine oil waste.